Smart nano-PROTACs reprogram tumor microenvironment for activatable photo-metabolic cancer immunotherapy - Zhang, Chi (2022)
Protease inhibitors can modulate intratumoral metabolic processes to reprogram the immunosuppressive tumor microenvironment (TME), which however suffer from the limited efficacy and off-targeted side effects. We report smart nano-proteolysis targeting chimeras (nano-PROTACs) with phototherapeutic ablation and cancer-specific protein degradation to reprogram the TME for photo-metabolic cancer immunotherapy. This nano-PROTAC has a semiconducting polymer backbone linked with a cyclooxygenase 1/2 (COX-1/2)-targeting PROTAC peptide (CPP) via a cathepsin B (CatB)-cleavable segment. CPP can be activated by the tumor-overexpressed CatB to induce the degradation of COX-1/2 via the ubiquitin-proteasome system. The persistent degradation of COX-1/2 depletes their metabolite prostaglandin E2 which is responsible for activation of immune suppressor cells. Such a smart PROTAC strategy synergized with phototherapy specifically reprograms the immunosuppressive TME and reinvigorates antitumor immunity.